Law as Narrative: Narrative Interpretation and Appropriation as an Element of Theft. (11th December 2018) - Cammiss, Steven
Abstract: The act requirement for the offence of theft requires that the defendant appropriates property belonging to another. The concept of appropriation, thought by the legislation's drafters to be straightforward, has proved to be difficult to interpret; controversies in the cases and commentary focus upon whether the consent of the owner is relevant to appropriation, and whether the concept includes an adverse interference with property rights. This paper explores these controversies through a different lens, that of law as narrative. Drawing upon law as literature, particularly law and narrative, I argue that narrative interpretations in law result in the creation of 'hard cases', where the application of appropriation, as envisaged by its framers, leads to difficult results. In so doing, I show how the normative syllogism is merely a justification for legal interpretation, with the law best understood in narrative terms. Applying the law is, therefore, not an exercise of correspondence between abstract law and particular facts, but instead an exercise in comparison between different narratives.